Efficient Utilization of Agricultural Land to Increase Food Crop Production in Golo Manting Village, Sano Nggoang District, West Manggarai Regency - Maria Cerliana Evavitri; Hamza Huri Wulakada; Poppy Haryani (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Efficiency in the utilization of agricultural land can affect population growth through food availability and reduce pressure on natural resources. The objectives of the research are (1) To analyze the factors affecting the efficiency of agricultural land use in Golo Manting Village, (2) To identify appropriate strategies to improve land quality. The research method used is a quantitative method with multiple regression analysis. The results of the study indicate that (1) The efficiency of agricultural land use in Golo Manting Village is influenced by various factors, but statistical tests show that land area, food crop production, and agricultural technology do not have a simultaneous effect. This indicates that other factors such as irrigation quality, type of fertilizer, planting patterns, and farmers' knowledge and skills are more dominant in determining the level of land efficiency (2) the use of modern agricultural technology effective land management can increase food crop production. (3) Agricultural intensification through the use of superior seeds, proper land management, and good fertilization can improve food crop production and the efficiency of agricultural land utilization. This research concludes that effective land management and the use of modern agricultural technology can enhance the efficiency of agricultural land use and food crop production in Golo Manting Village.